PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT) SUKU ANAK DALAM DI KECAMATAN KEMUNING OLEH DINAS SOSIAL KABUPATEN INDRAGIRI HILIR TAHUN 2021-2022 - Harahap, Siti Rahayu; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Empowerment is one of the functions of government. Empowerment is carried out by the Indragiri Hilir Regency Social Service to Remote Indigenous Communities (KAT), especially Suku Anak Dalam, which is the focus of this research. Remote Indigenous Community (KAT) is a group of people in certain numbers who are local and have not or little touched by the outside world such as services, socio-economics and politics. This research aims to find out the empowerment program carried out by the Indragiri Hilir Regency Social Service in the welfare of the Suku Anak Dalam (KAT) Remote Indigenous Community in Kemuning District. This research uses a qualitative approach by using descriptive research. Data collection techniques are carried out by interview and documentation. The data analysis technique used in this study has steps such as data collection, data reduction, data presentation and conclusion drawing. The results of this study explain that the empowerment stage is carried out with three stages, namely the awareness stage, the capacity stage, and the empowerment stage. The Remote Indigenous Community empowerment program for Suku Anak Dalam in Kemuning District has indeed been carried out by the Indragiri Hilir Regency Social Service. But the implementation is indeed less effective. This can be seen from the lack of participation of the Suku Anak Dalam community in the empowerment program by not carrying out the empowerment program on an ongoing basis, the assistance of the house is not effective. Keywords: Empowering the Community, Isolated Indigenous Communities, Suku Anak Dalam